2014
DOI: 10.1557/jmr.2014.105
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-based modeling of the impact response of a biomedical niobium–zirconium alloy

Abstract: This article presents a new multiscale modeling approach proposed to predict the impact response of a biomedical niobium-zirconium alloy by incorporating both geometric and microstructural aspects. Specifically, the roles of both anisotropy and geometry-based distribution of stresses and strains upon loading were successfully taken into account by incorporating a proper multiaxial material flow rule obtained from crystal plasticity simulations into the finite element (FE) analysis. The simulation results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Both calcium and silicon are indispensable constitutes of bone tissues as well as useful regulators of osteogenic differentiation. , In particular, Si ions are very capable to simultaneously accelerate bone calcification and stimulate vascular structure formation. As to ionic Zr, it was shown to cause toxicity in millimolar (mM) dosages . However, at lower concentrations, as is in our case (∼1.1 ppb per day), Zr ions are nonharmful and even exert bioactivity on bone-forming cells via activating BMP signaling .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Both calcium and silicon are indispensable constitutes of bone tissues as well as useful regulators of osteogenic differentiation. , In particular, Si ions are very capable to simultaneously accelerate bone calcification and stimulate vascular structure formation. As to ionic Zr, it was shown to cause toxicity in millimolar (mM) dosages . However, at lower concentrations, as is in our case (∼1.1 ppb per day), Zr ions are nonharmful and even exert bioactivity on bone-forming cells via activating BMP signaling .…”
Section: Discussionmentioning
confidence: 51%
“…As to ionic Zr, it was shown to cause toxicity in millimolar (mM) dosages. 63 However, at lower concentrations, as is in our case (∼1.1 ppb per day), Zr ions are nonharmful and even exert bioactivity on bone-forming cells via activating BMP signaling. 64 Additionally, the releasing of cation ions from calcium silicate materials is causative of mild alkalization of local milieus (Figure 8c), 56 and this can promote ALP expression and ECM mineralization.…”
Section: Discussionmentioning
confidence: 55%
“…As with other metals, the mechanical properties of Ti alloys can be improved through the use of mechanisms such as solid solution strengthening with interstitial and substitutional atoms, grain size refinement, particle precipitation, work hardening and dispersion strengthening. Onal et al proposed a multiscale modelling approach to predict the impact response of a biomedical Nb–Zr alloy by incorporating both geometric and microstructural aspects . They observed that composition and processing of metals and alloys may change their mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Onal et al proposed a multiscale modelling approach to predict the impact response of a biomedical Nb-Zr alloy by incorporating both geometric and microstructural aspects. 11 They observed that composition and processing of metals and alloys may change their mechanical properties. Annealed metal alloys, for instance, have better ductility than cold worked and cast materials, but, on the other hand, usually have lower tensile strength than cold worked ones.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that very large deformations taking place within very short time periods constitute the major difficulty of FE simulations of impact loading (Kormi et al, 1997;Raykhere et al, 2010;Onal et al, 2014). Specifically, the available time period is insufficient for the stabilization of the computed displacements in the case of impact loading, such that the material's behavior significantly deviates under this dynamic type of loading from that under normal conditions owing to the non-linear behavior under dynamic loading (Onal et al, 2014).…”
Section: Finite Element Simulations Of Experimental Impact Response Omentioning
confidence: 99%